Efek Jenis Rod dan Efisiensi Volumetrik pada Kinerja Pompa Angguk - Ilman Muhammad Azmi; Guguk Jatisukamto; Hary Sutjahjono (Proklamasi 45 University, 2020)
The productivity of the beam pump is influenced by the sucker rod type, material quality, and volumetric efficiency. Therefore, the beam pump should be designed to reach an optimum condition. The type of rod affects ability of the beam pump to lift liquid up from an oil reservoir to the surface as well as the horse power requirement to operate the pump. On the other hand, the productivity of the pump is also influenced by the characteristics of the reservoir rock and fluid such asreservoir productivity, gas liquid ratio, salinity and Hydrogen Sulfide (H2S) which are contained in the reservoir fluid. The purpose of this study is to observe Effect of Rod Type and Volumetric Efficiency on the Performance of a beam pump at X-1 well and production estimation in the future. In this research, several rod types were tested to find their liquid lifting efficiency. Based on result analysis, the highest production as well as liquid lifting efficiency is attained by applying ROD 96/05.The liquid production rate and lifting efficiency of the rod type are 1132 bpd and 15.6. The application of better quality sucker rod material (API grade D) and less corrosive fluid conditions (salt water) will be able to produce fluid with a higher flow rate. Furthermore, the effect of the crank-pitman ratio on the production rate is not large. Lower volumetric efficiency pumps require higher pump speed and horsepower to produce fluid with the same flow rate as high volumetric efficiency pumps. However, pumps with low volumetric efficiency have lower peak loads (PPRL).